2011
DOI: 10.1177/1557988311411909
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Challenge of Informed Decision Making in Prostate Cancer Community Outreach to African American Men

Abstract: African American men are disproportionately affected by prostate cancer. This project adopted a communitybased participatory approach to design and pilot test an educational outreach strategy that promotes informed decision making about screening among African American men in community settings in St. Louis, Missouri. Interviews with local subject matter experts informed the design of the strategy. The revised curriculum was pilot tested in 2009 with 63 men who completed pre-and posttest surveys that measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…In a recent systematic review of 397 papers (37 studies), which discussed recruitment strategies, money was shown to significantly improve recruitment of patients into clinical trials. 70 Other studies also have shown money to be a motivating factor. 71, 72 However, no prior studies found that money alone increased the recruitment of African Americans.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent systematic review of 397 papers (37 studies), which discussed recruitment strategies, money was shown to significantly improve recruitment of patients into clinical trials. 70 Other studies also have shown money to be a motivating factor. 71, 72 However, no prior studies found that money alone increased the recruitment of African Americans.…”
Section: Discussionmentioning
confidence: 98%
“…( Song et al, 2015 ). Prostate cancer information also can be successfully shared via interpersonal communication in familiar cultural settings such as barbershops, churches, and fraternal group meetings ( Cowart, Brown, & Biro, 2004 ; Meade, Calvo, Rivera, & Baer, 2003 ; Releford, Frencher, & Yancey, 2010 ; Woods et al, 2004 ; Wray, Vijaykumar, Jupka, Zellin, & Shahid, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies specifically noted the importance of stressing early detection of prostate cancer in communication to Black men ( Drake et al, 2010 ; Griffith et al, 2007 ; Kripalani et al, 2007; Miller et al, 2014; Odedina, Campbell, LaRose-Pierre, Scrivens, & Hill, 2008 ; Wray et al, 2011 ). In particular, participants in Griffith et al’s (2007) study said that Black men need to know that early detection gives them options and that having prostate cancer does not mean losing control over one’s life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When deciding whether or not to participate in PCa screening, knowledge is crucial to the decision-making process. 9 Wray et al 11 reported low levels of knowledge among most AA men about PCa, risk factors, screening and treatment options. Oliver, et al 10 found that “not understanding what was involved in PCa screening”, and beliefs about pain and embarrassment were reported by rural AA men as reasons for not participating in PCa screening.…”
Section: Prostate Cancermentioning
confidence: 99%